Perceptions of High School Geography Teachers in Langkat Regency Towards Augmented Reality Media on Hydrosphere Content in Improving Critical Thinking Abilities - Salmayda Salmayda; Tuti Mutia; Muhammad Rizieq Fahmi; Khoirunnisaa’ Khoirunnisaa’ (Universitas Pendidikan Indonesia, 2023)
Augmented Reality (AR) is a technology that has the opportunity to improve critical thinking skills in Geography learning. This research aims to investigate the perceptions of Geography teachers in Langkat Regency regarding using AR media in hydrosphere material to enhance critical thinking skills and explore the difficulties of geography teachers in implementing AR in Geography learning. This research uses quantitative descriptive research with survey methods. The research sample consisted of 43 geography teachers in Langkat Regency. The data analysis technique used is descriptive analysis. Based on the research results, geography teachers in Langkat Regency positively perceive the use of AR in Geography learning. Most teachers know AR's opportunities to improve students' critical thinking skills and are interested in using AR as a medium for learning hydrosphere material. The investigation results also show obstacles to integrating AR in Geography learning, namely the availability of school infrastructure and limited venues for holding activities to increase teacher competency.